Thrombus in the left atrial septal pouch mimicking myxoma. Issue 3 (27th August 2013) - Shimamoto, Keiko; Kawagoe, Takuji; Dai, Kazuoki; Inoue, Ichiro
ABSTRACT A 15 × 13 mm mobile ovoid mass attached via a 15 × 5 mm stalk to the interatrial septum in the left atrium was detected on transesophageal echocardiography and was diagnosed as a myxoma in a 70‐year‐old woman with chronic atrial fibrillation. She was prescribed anticoagulant therapy with warfarin before elective cardiac surgery and demonstrated no thromboembolic event during a 2.5‐month period. Preoperative transesophageal echocardiography showed the disappearance of the intracardiac mass and the presence of a left atrial septal pouch, suggesting that the initial image was a thrombus originating from the left atrial septal pouch. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:185–188, 2014